Effect of cuttings defoliation and different substrates on the vegetative propagation of the monkey-pepper (Piper aduncum L.) (Piperaceae) - Ferriani, Aurea Portes; Krinski, Diones (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
Forests constitute a valuable natural resource, especially when including non-timber forest products (NTFPs). Bioprospecting for and sustainable exploration of native species and the development of protocols for seedling production promote conservation. Piper aduncum L. stands out in several regions of Brazil because of several biological activities, notably action as a repellent, antimicrobial and insecticide. This study aimed to evaluate the influence of defoliation and different substrates on the cutting process. For this, an experiment was conducted in February, 2016 at the Health Plant Department, Sector of Agricultural Sciences, Federal University of Paraná (UFPR). Piper aduncum stem cuttings with 10 cm and 1/3 of the leaf area and defoliated cuttings. Stem cuttings were washed in running water for 5 minutes for subsequent use in three different substrates (medium sand sifted, vermiculite and commercial substrate Tropstrato HP®). The experiment design was completely randomized in a 2×3 factorial arrangement (cutting type x substrate), and it was evaluated the rooting percentage, mortality, shoot emission, number of roots and average length of the three largest roots after 60 days. The results confirmed that the presence of leaves in P. aduncum stem cuttings promotes adventitious rooting. The different substrates did not exert a significant influence on the performance of the cuttings in this species.